PERANCANGAN DAN PEMBANGUNAN APLIKASI UJIAN ONLINE PADA NEUMANN ENGLISH COURSE DENGAN METODE RANDOM - Jenny Veronika Ginting; Meiliana Br. Sembiring (UPPM, 2016)
Exam is one way to evaluate the learning process of the learners. Trials were carried out manually have some constraints. Factors customs fraud and cheating is the greatest obstacle. along with the development of information technology, the conventional exam shifted to online examination system. With the current technological developments which require a test system that is efficient, effective, and able to carry out testing quickly and accurately, it is expected that all theconstraints typically encountered by lecturers and students at the time of execution of manual tests, such as the shortage of paper or not legible hand writing, can be reduced or even eliminated with the establishment of an online exam application. Neumann English course (NEC) has 4 levels. At this online exam application, provided 240 questions. Which in each have 60 questions that then at random and at select 40 questions as a test for each examines NEC. Applications online exam Neumann English Course (NEC) is built by a random method that serves to randomize the exam participants, so the exam that was done by the examinees varies. Making the application will use the programming language PHP and MySQL for database creation.